Interaction of central kisspeptin with melanocortin, GABAergic, corticotrophin, and NPY systems on food intake in chickens - Ahmadreza Kord; Bita Vazir; Morteza Zendedel kheybari; Vahab Babapour; Ahmad Asghari (The Iranian Journal of Veterinary Science and Technology, 2022)
Kisspeptin is a key component of reproduction that can directly affect food intake in mammals. There is evidence suggesting that melanocortin, GABA, corticotrophin, and neuropeptide Y (NPY), have a mediatory role in reward; however, how these substances interact with kisspeptin-induced by food intake in birds, remains to be identified. Accordingly, in this study,   a total of 10 experiments were carried out to investigate the interplay  between kisspeptin and these systems for the control of food intake in neonatal layer-type chickens. In the first experiment, chickens were intracerebroventricular (ICV) injected with saline and Metastin (Kisspeptin, 0.25, 50, and 1 nmol). In the second experiment, saline, Metastin (1 nmol), BIBP-3226 (NPY1 receptor antagonist, 1.25 nmol), and co-injection of Metastin + BIBP-3226 were injected. Experiments 3-10 were similar to experiment 1, except that chickens received BIIE 0246 (NPY2 receptor antagonist, 1.25 nmol), CGP71683A (NPY5 receptor antagonist, 50 μg), Picrotoxin (GABAA receptor antagonist, 1.25 nmol), CGP54626 (GABAB receptor antagonist, 21 µg), astressin-B (CRF1 / CRF2 receptor antagonist, 30 µg), Astressin2-B (CRF2 receptor antagonist, 30 µg), SHU9119 (MC3 / MC4 receptor antagonist, 0.5 nmol), and MCL0020 (MC3 / MC4 receptor antagonist, 0.5 nmol) instead of BIBP-3226. Food intake was subsequently assessed until 120 min after the injection. Based on the findings, Metastin (0.25, 50, and 1 nmol) significantly increased food intake in a dose-dependent manner (p < 0.05). However, BIBP-3226 and Picrotoxin inhibited Metastin-induced hyperphagia in neonatal chickens (p < 0.05); Whereas, whereas BIIE 0246, CGP71683A, CGP54626, astressin-B, astressin2-B, SHU9119, and MCL0020 had no effect (p > 0.05). These results showed that the effect of kisspeptin on food intake might be mediated by NPY1 and GABAA receptors in layer-type chickens.